OPTIMALISASI USAHA BUDIDAYA IKAN KOI DI TASIKMALAYA DENGAN KONSEP INTEGRATION SYSTEM (STUDI KOMPREHENSIF PADA UNIT USAHA DRA KOI DAN RF GUSTAMAN GROUP) - Mulyana, Defri; Saepulloh, Asep; Ahmad, Alex Anis; Roswita, Lilis; Gustaman, Randy Fadillah (Jurnal Pengabdian Masyarakat Indonesia, 2023)
Fish cultivation is an appropriate alternative in an effort to increase fisheries production, both quantity and quality. One type of freshwater ornamental fish that is very popular with the public is the koi fish (cyorinus carpio). Koi fish are usually used as decoration for ponds at home, because koi fish have beautiful colors, so they can relieve stress for their owners and koi fish are even considered a fish that can bring good luck to their owners. The bright color of koi fish can calm the mind, emotions and heart of its owner, this is what makes koi fish have many fans among ornamental fish. Based on observations made by the service team, the problem found in partners was that the koi fish cultivating partner group did not understand the process of cultivating koi fish effectively and efficiently, starting from selecting quality koi broodstock, maintaining genetics of broodstock, selecting koi fish offspring to marketing channels. Koi fish. Koi fish cultivator groups in Tasikmalaya City need comprehensive and continuous assistance. Academics also need to play a role in the development process of koi fish farmers so that the koi fish harvest can be met according to market expectations and cultivation can be effective and efficient so that groups of farmers can improve their welfare. The problems found by the community service team at Mitra DRA KOI and RF Gustaman Group were then analyzed so that the team proposing community service for the Community Partnership Program (PKM) scheme offered several alternative solutions, including: First, providing training on koi fish cultivation from seeding to harvest; Second, entrepreneurial management and marketing training using online media.